The Role of Concentration Ratio of TTiP:AcAc on the Photocatalytic Activity of TiO2 Thin Film in Reducing Degradation Products of Used Frying Oil - Ummi Kaltsum; Affandi Faisal Kurniawan; Iis Nurhasanah; Priyono Priyono (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The TiO2 thin film has been applied to reduce degradation products (free fatty acid/FFA and peroxide value/PV) in used frying oil under ultraviolet (UV) light irradiation. FFA and PV are degradation products in used frying oil that can cause various diseases in human. In this study, the TiO2 thin films were made from precursor solution with concentration ratio of titanium tetraisopropoxide (TTiP) and acetylacetone (AcAc) of 1:1, 1:2, 2:1, 2:3, and 3:2. The aim of this study is to investigate the effect of concentration ratio of TTiP and AcAc on the photocatalytic activity of TiO2 thin film in reducing FFA and PV of used frying oil. The spray coating method was used to deposit precursor solution of TiO2 onto glass substrate at 450 oC. All TiO2 thin films consist of spherical-like grain with dominant structure of TiO2 rutile. The band gap energy of TiO2 thin films was in the range 3.11-3.16 eV. Concentration ratio of TTiP and AcAc of 2:3 results in TiO2 thin film with highest photocatalytic activity in reducing FFA and PV of used frying oil.